ANALISA PRA STUDI KELAYAKAN DAN MASTER PLAN KAWASAN INDUSTRI BERBASIS PEDESAAN DI KABUPATEN KONAWE SELATAN - Azis, Rudi; Asrul, Asrul; Tadung, Edy; Wahyuddin, M. (Aksara Public, 2019)
Abstract Rural development is a major part of national development and is even an indicator of development as measured by per capita income and the Human Development Index. One such concrete manifestation is the rural development approach that is based on industrial products or rural potential. Therefore, it is necessary to develop the concept of a rural-based Industrial Zone. The purpose of this study is to analyze the feasibility of the location as an industrial area, give direction to the realization of spatial plans, especially in the area of ​​industrial designation and analyze the potential of Agroindustrial Park in Konawe Selatan District. This study uses a quantitative analysis method with Location Quotient (LG) approach and Shift share analysis for Analysis of potential regions. Location determination based on location sampling in the agropolitan and minapolitan areas based on the Konawe Selatan District RTRW. The results of the study concluded that the development of Agroindustrial Park in Laeya Sub-district with the support of a development area of ​​1000 Ha in which there was a rice field area as a source of industrial raw materials and industrial processing area of ​​5 hectares. and Lalembu Subdistrict, the institutional system in the development of Industrial Estates in Konawe Selatan District uses a triple helix model, which is an institution that relies on the synergy of roles between Government, society and Industry.